Pola Penyebaran Hoaks pada Kalangan Mahasiswa Perguruan Tinggi Islam di Bandung Jawa Barat - Moh. Dulkiah; Paelani Setia (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
The phenomenon of hoaxes as fake news is mostly constructed through social media in this era. The sites that produce and spread hoaxes or fake news are relatively high in several big cities in Indonesia, especially Bandung, the capital of West Java. A large number of false reports have made the public uneasy. The hoax news is not only consumed by the general public but also among universities. This study aims to determine how the hoax model spread among Muslim students in Islamic universities in Bandung. This research uses a qualitative approach. The data was collected by applying in-depth interviews and documentation studies to explore the focus of the research. This study found several facts, namely: first, most of the students often received hoaxes, even some students had also been hoax makers and spreaders. Second, the spread of hoaxes is carried out through social media in line with information technology development. Third, there are 3 (three) patterns of hoax spreading among Islamic university students, namely (1) the pattern of cyclization or distribution carried out within certain groups; (2) general public distribution patterns; (3) a break pattern, in which the dissemination of information stops to the authorities. Besides, the campus needs support in strengthening digital literacy practices and comprehensive verification (tabayun) efforts for students, and serious handling of the government.